2022
DOI: 10.1039/d2se00399f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotreating of bio-crude obtained from hydrothermal liquefaction of biopulp: effects of aqueous phase recirculation on the hydrotreated oil

Abstract: Aqueous phase recirculation (APR) during the hydrothermal liquefaction (HTL) process is a means to enhance HTL performance and lower the need for intensive residual water treatment. However, the obtained HTL...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The flask was placed in an oven at 70 • C to dry the contents until a constant weight was reached. The crude protein content (CP) was estimated by multiplying the nitrogen content of the bio-waste by a 6.25 (Kohansal et al, 2022;Mariotti et al, 2008). Following the US Food and Drug Administration (FDA) [21 CFR 101.9(c)(6)(i)-(iv)] instructions, the carbohydrate content was calculated based on:…”
Section: Analysis Of the Feedstock And Productsmentioning
confidence: 99%
See 3 more Smart Citations
“…The flask was placed in an oven at 70 • C to dry the contents until a constant weight was reached. The crude protein content (CP) was estimated by multiplying the nitrogen content of the bio-waste by a 6.25 (Kohansal et al, 2022;Mariotti et al, 2008). Following the US Food and Drug Administration (FDA) [21 CFR 101.9(c)(6)(i)-(iv)] instructions, the carbohydrate content was calculated based on:…”
Section: Analysis Of the Feedstock And Productsmentioning
confidence: 99%
“…Recently, the effect of aqueous phase recirculation (APR) on HTL has received some attention, and few solutions have been suggested (Harisankar et al, 2021;Kohansal et al, 2021;Leng et al, 2020;Zhu et al, 2015). Pedersen's Group investigated a two-stage process by integrating the APR with HTL process for wet biowaste (bio-pulp), and subsequently hydrotreating the bio-crude obtained over sulfided NiMo/Al 2 O 3 catalyst (Kohansal et al, 2022). Interestingly, the findings showed that the APR exhibited a promising result in terms of bio-crude yield and energy recovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, quantifying the vast numbers of compounds detected in heterogeneous bio-oils requires the construction of a large calibration dataset. [10][11][12] Depending on the GC-MS column, compounds present, and their concentrations, derivatization may be necessary to improve identication, reproducibility and therefore nal quantication of species present. 6,13,14 Derivatization requires its own calibration to quantify derivatized peaks, sometimes at different operating conditions than the nonderivatized analysis.…”
Section: Introductionmentioning
confidence: 99%